'All you need is brand love': a critical review and comprehensive conceptual framework for brand love. Issue 1 (2nd January 2019) - Palusuk, Narissara; Koles, Bernadett; Hasan, Rajibul
ABSTRACT: Brand love has received increasing attention given its potential to enhance customer engagement, brand advocacy, commitment and loyalty. Despite its relevance, few studies explore brand love per se, and existing conceptualisations remain sporadic and fragmented. The purpose of the current paper is to critically assess available work on brand love, reviewing conceptualisations, measurements and key proximal constructs. Expanding upon and synthesising earlier work and conceptualisations, we develop and propose a comprehensive conceptual framework for brand love that is innovative for the following reasons. In particular, our model takes a developmental rather than a snapshot approach to capture brand love trajectories as a function of their onset and evolution; incorporates key frameworks and as such builds on interpersonal, parasocial and experiential theories; and acknowledges the important role of brand hate. Managerial implications and future research directions are discussed.